Studi Numerik Pengaruh Sudut Kemiringan Push Nozzle pada Air Curtain Terhadap Pola Aliran Push-Pull Ventilation - Muhammad Rafli Syahrizal R; Burniadi Moballa; Agung Purwana (Politeknik Perkapalan Negeri Surabaya, 2023)
COVID-19 cases will continue to spread throughout the world until 2023, including inIndonesia, and have many negative impacts, especially for the industrial world because it is difficultto enforce a minimum distance of 1-2 meters between employees. One technology that has highpotential to be applied is the air curtain. This journal analyzes push-pull ventilation to protectworkers from microdroplet inhalation. In this study, two variations of the push-pull ventilation speedratio (Vs/Vb) were used, namely 4 and 6. As well as using a variation of the push nozzle slope, namely10°. In this study, running was carried out with two models, namely modeling without a mannequinand with a mannequin. To complete this research, simulations were carried out using theComputational Fluid Dynamics (CFD) method using Salome, OpenFOAM, and ParaView software.So, the results obtained in modeling without a mannequin, the speed ratio of 6 is the most optimalratio with the least amount of average discharge that goes out of bounds, namely 0.582 m3/s. Whilethe results of the push-pull modeling with the mannequin show that no droplets penetrate the aircurtain at all variations of the velocity ratio, the velocity ratio of 6 is the velocity ratio that has aover-blow flow pattern that is very effective in holding down spray from droplets.